Tinjauan Tentang Perjanjian Pengikatan Jual Beli Hak Milik Atas Tanah Berdasarkan Akta Notaris Di Kota Banjarmasin - , Sumalia Novia. SH. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The research on preliminary sale and purchase binding agreement of right on land based on notariel deed in Banjarmasin was intended to study legal power of sales and purchase binding agreement of right on land based on notarial deed, and to identify legal protection received by partied in the sales and purchase binding agreement based on notarial deed. It was juridicial empirical law research. Juridicial empirical study will identify and concept law as real and functional social institution in pattern living system. As juridical study it used approach of using laws and legal norm according to the issue, while empirical approach emphasize existing problem, while empirical approach emphasize study to obtain empirical knowledge with direct involvenment to its object. The research was presented in descriptive analytical report, where processed data was analyzed qualitatively. Result of research were follow : 1). A legal power of sales and purchase binding agreement of rigth on land is very strong, because the agreement is made based on notarial deed that is authentic deed having perfect proving power. 2) Legal protection for parties in sales and purchase binding agreement of right on land seen from position of the agreement. When the agreement was made unofficially, its legal protection follows legal protection of unofficial agreement. When, the sales and purchase binding agreement is made before or by authoritative official (notary) or is made based on notarial deed, the deed is notarial deed that has protection power according to protection for authentic deed.